2020
DOI: 10.1504/ijmfa.2020.106999
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of XBRL adoption: a meta-analysis

Abstract: eXtensible Business Reporting Language (XBRL) is a new technology revolutionising the world of business information. Past studies attempt explaining what are the factors, such as drivers and inhibitors, able to exert influence over the adoption of this technology. To date, findings seem contrasting. This fragmented panorama provides the opportunity to current study, which purpose is to provide a fine-tuned meta-analysis of determinants of XBRL adoption, by cross-checking the results of 18 prior contributions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The TOE framework is, therefore, more applicable to firm-level decisions rather than a country-level decisions. Consequently, studies on country-level decisions to adopt a specific technology apply the institutional theory (Abdullah et al , 2009; Ansary et al , 2020). Given that our study is a country-level analysis, we refer to the institutional theory as a fundamental theoretical framework to examine the country-level factors associated with XBRL adoption.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The TOE framework is, therefore, more applicable to firm-level decisions rather than a country-level decisions. Consequently, studies on country-level decisions to adopt a specific technology apply the institutional theory (Abdullah et al , 2009; Ansary et al , 2020). Given that our study is a country-level analysis, we refer to the institutional theory as a fundamental theoretical framework to examine the country-level factors associated with XBRL adoption.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Recently, studies have adopted the TOE framework based on its strengths over the DOI Model (Al Mudawi et al, 2022; Ansary et al, 2020; Basuony et al, 2021; Krieger et al, 2021; Siew et al, 2020; Yau‐Yeung et al, 2020; Zhang et al, 2020). The TOE framework is unique in explaining the broad technological, organizational, and environmental factors of firms (Siew et al, 2020; Venkatesh & Bala, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notable among these frameworks are the DOI theory (Rogers, 1983) and the TOE framework (Tornatzky et al, 1990). However, other researchers argue that the DOI does not fully explain the innovation adoption and diffusion within organizations (Al Mudawi et al, 2022; Ansary et al, 2020; Brancheau & Wetherbe, 1990; Krieger et al, 2021). Additionally, it is essential to note that the variables of the DOI theory are unlikely to be significant determinants of technology adoption and acceptance and thus, some researchers suggest the inclusion of new variables either as independent or control variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…XBRL is a new concept in corporate reporting and the perceived usefulness of its benefits depends on the awareness among various stakeholders (Henderson et al , 2012). As a result, numerous authors undertook the study of XBRL awareness and understanding among corporate accountants, auditors, preparers and regulators (Ansary et al , 2020). The prior literature showed that several studies have investigated the awareness and understanding of XBRL among professional accountants and reported low to moderate levels of awareness (Nel and Steenkamp, 2008; Eni, 2015; Lalević Filipović et al , 2018; Helfaya and Amin, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Challenges with XBRL can impede adoption efforts, particularly when we consider the practical implications of the standards and methods of financial reporting. Previously, researchers provided excellent insights related to the general challenges of adopting XBRL (Ansary et al , 2020). However, there is a lack of research focusing on the issues in the post-XBRL mandate context.…”
Section: Introductionmentioning
confidence: 99%